The naked nude - Borzello, Frances (Thames & Hudson, 2012)
"The representation of the nude in art remained for many centuries a victory of fiction over fact. Beautiful, handsome, flawless--its great success was to distance the unclothed body from any uncomfortably explicit taint of sexuality, eroticism or imperfection. Here Frances Borzello contrasts the civilized, sanitized, perfected nude of Kenneth Clark's classic, The Nude: A Study in Ideal Form (1956), with today's depictions: raw, uncomfortable, both disturbing and intriguing. Grittier and more subtle, the new nude asks awkward questions and behaves provocatively. It is a very naked nude, created to deal with the issues and contradictions that surround the body in our time"--Jacket.